High-safety sodium ion battery electrolyte and battery

By adding a polycyclosiloxane monomer that is easy to open-polymerize in the sodium ion battery electrolyte, a high-stability negative electrode-electrolyte interface layer is constructed, which solves the thermal runaway problem of sodium ion battery and improves the thermal safety of the battery and Stability repairs the rupture of the electrolyte interface layer and prevents the continuation of thermal runaway.

CN119297412APending Publication Date: 2025-01-10ANHUI HUA NA NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411409371.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The thermal runaway problem of sodium ion batteries has not been fully studied, especially in the initial stage, the prior art is difficult to effectively suppress the exothermic side reaction between hard carbon negative electrode and electrolyte, resulting in a high risk of safety accidents.

Method used

Add an easily ring-opening polymerized organic trimetal ring or tetrametal cyclosiloxane monomer to the electrolyte solution to build a highly stable negative electrode-electrolyte interface layer, and form a hard carbon adhered to the ring-opening polymerization of polycyclosiloxanes. The high specific heat-capacity polymer passivation layer on the surface blocks the exothermic side reaction of the negative electrode and the electrolyte, and generates SiO2 at high temperature to retardant flame.

Benefits of technology

It effectively increases the self-extrogenic temperature of the battery, suppresses the occurrence of thermal runaway, repairs the negative impact of HF produced by hydrolysis, and enhances the stability of the negative electrode-electrolyte interface layer and the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297412A_ABST
    Figure CN119297412A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of chemical power sources and energy storage, and particularly discloses a high-safety sodium ion battery electrolyte and a battery, and the electrolyte comprises a sodium salt, a carbonate solvent and polycyclic siloxane. When a negative electrode-electrolyte interface layer is decomposed, a fresh hard carbon surface is exposed, and the temperature of the battery also reaches a ring opening temperature, so that a three-membered ring or four-membered ring siloxane monomer is subjected to ring opening polymerization to generate a passivation layer covering the hard carbon surface, the negative electrode-electrolyte interface layer is protected, heat release side reaction of a negative electrode and electrolyte is inhibited, and the service life of the battery is prolonged. The three-membered ring or four-membered ring siloxane generates SiO2 at high temperature, and further development of thermal runaway is prevented; the stability of the negative electrode-electrolyte interface layer of the sodium-ion battery and the safety of the battery can be improved at the same time, and other prior art cannot give consideration to the stability; according to the invention, the damaged negative electrode-electrolyte interface layer can be repaired in real time, and thermal runaway can be inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical power sources and energy storage, and in particular relates to a highly safe sodium ion battery electrolyte and a battery. Background Art

[0002] In the early 2020s, the price of raw materials for lithium-ion batteries rose and lithium resources were insufficient. Sodium-ion batteries, with their abundant resources and uniform global distribution, low cost, relative safety, and good low-temperature fast charging performance, have won the attention and favor of the energy storage market and have risen again. However, the research on the thermal runaway problems and paths of sodium-ion batteries is still insufficient, and no consistent conclusion has been reached. The society needs to pay close attention to reduce and avoid safety accidents. According to the time series diagram of the development of thermal runaway, the exothermic side reaction of the hard carbon negative electrode and the electrolyte is the main cause of the early thermal runaway. The construction of a stable negative electrode-electrolyte interface layer can effectively inhibit the exothermic side reaction of the hard carbon and the electrolyte, increase the self-heating starting temperature, and improve the thermal safety of the battery.

[0003] The negative electrode-electrolyte interface layer of sodium-ion batteries is composed of organic and inorganic phases. The organic component has poor thermal stability. The main components of the inorganic phase are sodium carbonate and sodium fluoride, which are more soluble in the electrolyte than lithium salts. The negative electrode-electrolyte interface layer is more unstable than that of lithium-ion batteries as a whole, so the view that sodium-ion batteries are safer than lithium-ion batteries cannot be fully affirmed. In addition, when there is a small amount of water inside the battery, NaPF6 hydrolyzes to produce HF, which will destroy the negative electrode-electrolyte interface layer. If a stable inorganic component can be added to the negative electrode-electrolyte interface layer and the negative electrode-electrolyte interface layer that has been broken by thermal decomposition can be repaired in time, the exothermic side reaction between the hard carbon negative electrode and the electrolyte can be effectively suppressed, and the continuation of thermal runaway can be cut off.

[0004] The methods for avoiding thermal runaway in sodium-ion batteries can be borrowed from those in lithium-ion batteries, such as adding flame retardants, coating insulating layers, improving electrolyte salts, modifying diaphragms, forced fire extinguishing and cooling, and isolating battery packs. However, most methods focus on solving the mid-term, severe, and late stages of thermal runaway, and there are few technologies that start from the initial stage of thermal runaway. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a highly safe sodium ion battery electrolyte and battery, by adding organic three-membered ring or four-membered ring siloxane monomers that are easily ring-opened and polymerized due to angular tension to the electrolyte to construct a highly stable negative electrode-electrolyte interface layer.

[0006] In order to achieve the above objectives, one of the technical solutions of the present invention is: a highly safe sodium ion battery electrolyte, comprising a sodium salt, a carbonate solvent, and a polycyclic siloxane.

[0007] In a preferred embodiment of the present invention, the sodium salt is selected from sodium hexafluorophosphate or sodium perchlorate.

[0008] In a preferred embodiment of the present invention, the carbonate solvent is selected from two or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and propylene carbonate.

[0009] Further preferably, the volume fractions of the various carbonate solvents are equal.

[0010] In a preferred embodiment of the present invention, the polycyclic siloxane is an organic small molecule monomer, a carbon chain is bonded to the polycyclic ring, the carbon chain contains fluorine atoms and silicon-oxygen bonds, and is liquid or solid at room temperature.

[0011] More preferably, the polycyclic ring in the polycyclic siloxane is a three-membered ring or a four-membered ring.

[0012] In a preferred embodiment of the present invention, the concentration of sodium salt in the electrolyte is 0.5-3M.

[0013] In a preferred embodiment of the present invention, the content of polycyclic siloxane in the electrolyte is 5-10 Vol%.

[0014] In a preferred embodiment of the present invention, the electrolyte is prepared in an argon atmosphere with O2<0.5ppm and H2O<0.5ppm and stirred for 16-24h to make it uniformly mixed.

[0015] In a preferred embodiment of the present invention, the electrolyte further comprises a dissolving agent.

[0016] Further preferably, the dissolution promoter is selected from one or more of hydrofluoroethers such as 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, tris(trifluoroethoxy)methane, 1,1,1,3,3,3-hexafluoroisopropyl methyl ether, 1H,1H,5H-octafluoropentyl 1,1,2,2-tetrafluoroethyl ether and fluorinated aromatic 1,2-2 fluorobenzene.

[0017] In a preferred embodiment of the present invention, if the electrolyte is separated into layers after standing for 2-4 hours, 15-30 Vol% of a dissolving agent is added, and stirring is continued for 4-6 hours; if the electrolyte is not separated into layers after standing, no dissolving agent is added.

[0018] In order to achieve the above objectives, the second technical solution of the present invention is: a sodium ion battery, comprising the above-mentioned high-safety sodium ion battery electrolyte.

[0019] In a preferred embodiment of the present invention, the battery is made by lamination, injecting a highly safe sodium ion battery electrolyte in an argon atmosphere with O2<0.5ppm and H2O<0.5ppm, and heat-sealing after standing in vacuum for 6-10 hours.

[0020] In a preferred embodiment of the present invention, the battery includes a positive electrode, a negative electrode and a separator, the positive electrode is one of sodium nickel iron manganate, sodium nickel manganate, sodium manganate, sodium iron phosphate, sodium vanadium phosphate or sodium iron pyrophosphate, and the negative electrode is hard carbon; the separator is a polyolefin, preferably a polyethylene separator or a ceramic separator.

[0021] In a preferred embodiment of the present invention, the injection coefficient of the electrolyte in the battery is 1.5-2.5 mL / Ah.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention contains SiO2 generated by conversion of siloxane in the negative electrode-electrolyte interface layer of the battery at room temperature. x When the internal temperature of the battery rises to the point where the negative electrode-electrolyte interface layer begins to decompose, the three-membered ring or four-membered ring siloxane undergoes ring-opening polymerization to form a polymer passivation layer with high specific heat capacity and high thermal stability attached to the hard carbon surface, which blocks the exothermic side reactions of the negative electrode and the electrolyte, increases the self-exothermic temperature of the battery, and prevents thermal runaway.

[0024] 2. The polycyclic siloxane of the present invention generates SiO2 at high temperature to achieve a flame retardant effect;

[0025] 3. When a small amount of water is contained inside the battery of the present invention and NaPF6 is hydrolyzed to produce HF, the polycyclic siloxane reacts with HF and opens the ring, thereby preventing HF from damaging the negative electrode-electrolyte interface layer and suppressing the negative impact of hydrolysis;

[0026] 4. The present invention can simultaneously improve the stability of the negative electrode-electrolyte interface layer and the battery safety of the sodium ion battery, while other existing technologies cannot take both into account;

[0027] 5. The present invention can repair the damaged negative electrode-electrolyte interface layer in real time and inhibit the occurrence of thermal runaway. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The battery cycle performance of Example 1, Comparative Example 1 and Comparative Example 2 with different electrolyte compositions is compared, and the current density is 2.0 mA / cm 2 , surface capacity is 2.0mAh / cm 2 ;

[0029] Figure 2The thermal stability test results of the two electrolytes and the charged negative electrode powder of Example 2 and Comparative Example 3;

[0030] Figure 3 The scanning electron microscope image (a) of the fully charged hard carbon of Example 2 after cycling in the electrolyte of the present invention is given, and the scanning electron microscope image (b) of the fully charged hard carbon of Comparative Example 3 after cycling in the 1MNaPF6, EC:DEC=1:1Vol% electrolyte is given;

[0031] Figure 4 These are the thermal runaway test results of the battery cells with the two electrolytes in Example 3 and Comparative Example 4. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is described in more detail below with reference to the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0033] A highly safe sodium ion battery electrolyte comprises sodium salt, carbonate solvent and polycyclic siloxane.

[0034] The sodium salt is selected from sodium hexafluorophosphate or sodium perchlorate.

[0035] The carbonate solvent is selected from two or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and propylene carbonate.

[0036] The volume fractions of the various carbonate solvents are equal.

[0037] The polycyclic siloxane is an organic small molecule monomer, with a carbon chain bonded to the polycyclic ring, the carbon chain containing fluorine atoms and silicon-oxygen bonds, and is liquid or solid at room temperature.

[0038] The polycyclic ring in the polycyclic siloxane is a three-membered ring or a four-membered ring.

[0039] The concentration of sodium salt in the electrolyte is 0.5-3M.

[0040] The content of polycyclic siloxane in the electrolyte is 5-10 Vol%.

[0041] The electrolyte was prepared in an argon atmosphere with O2<0.5ppm and H2O<0.5ppm and stirred for 16-24h to make it uniformly mixed.

[0042] The electrolyte further includes a dissolving agent.

[0043] The dissolution promoter is selected from one or more of hydrofluoroethers such as 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, tris(trifluoroethoxy)methane, 1,1,1,3,3,3-hexafluoroisopropyl methyl ether, 1H,1H,5H-octafluoropentyl 1,1,2,2-tetrafluoroethyl ether and fluorinated aromatic 1,2-2 fluorobenzene.

[0044] If the electrolyte is separated into layers after standing for 2-4 hours, 15-30 Vol% of a dissolving agent needs to be added, and stirring is continued for 4-6 hours; if the electrolyte is not separated into layers after standing, no dissolving agent needs to be added.

[0045] A battery comprising the above-mentioned high-safety sodium ion battery electrolyte.

[0046] The battery is made by stacking, injecting a highly safe sodium ion battery electrolyte in an argon atmosphere with O2<0.5ppm and H2O<0.5ppm, and heat-sealing after standing in vacuum for 6-10 hours.

[0047] The battery comprises a positive electrode, a negative electrode and a separator. The positive electrode is one of sodium nickel iron manganate, sodium nickel manganate, sodium manganate, sodium iron phosphate, sodium vanadium phosphate or sodium iron pyrophosphate, and the negative electrode is hard carbon. The separator is a polyolefin, preferably a polyethylene separator or a ceramic separator.

[0048] The electrolyte injection coefficient in the battery is 1.5-2.5 mL / Ah.

[0049] In the following specific implementation manner, the positive electrode active material is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, the conductive agent is conductive carbon black, the binder is polyvinylidene fluoride, the weight ratio of the three is 96:2:2, the negative electrode active material is hard carbon, the conductive agent is conductive carbon black, the binder is polyvinylidene fluoride, the weight ratio is 95:2:3, the N / P ratio of the battery cell is 1.06, the diaphragm is a wet PE diaphragm, both the positive and negative electrodes use aluminum ears, and the design capacity is 1Ah.

[0050] Example 1

[0051] First, weigh 0.01mol NaPF6, take 5mL EC and 5mL DEC, mix the above three evenly, and prepare 1M NaPF6, EC:DEC = 1:1 Vol% electrolyte; then add 0.5mL trifluoropropyl methyl cyclotrisiloxane, stir at room temperature for 24h, let stand for 3h, then separate, add 2mL 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and stir for another 5h. Inject 2mL of the electrolyte into the battery cell, let stand in vacuum for 8h, then heat seal, and let stand for another 24h.

[0052] Cycling conditions of the battery: 0.2 mA / cm 2 Activated for 3 cycles at a current density of 2.0 mA / cm 2 The current density is cycled 300 times, constant current and constant voltage are charged to 4V, the cut-off current is 1 / 10 of the original, and constant current is discharged to 2V.

[0053] Example 2

[0054] The battery cell that has completed the cycle in Example 1 is charged to 4V, the battery cell is disassembled in an argon glove box, the negative electrode is taken out, the charged hard carbon powder is scraped off, and the electrolyte of the battery cell in Example 1 is placed in a sealed crucible at a ratio of 1 mg hard carbon powder: 1 μL for thermal stability test, and part of the remaining hard carbon is taken for scanning electron microscopy observation.

[0055] Thermal stability test conditions: heating to 400°C, heating rate 5°C / min, argon atmosphere.

[0056] Example 3

[0057] A soft-pack battery as described in Example 1 was manufactured, and after 10 cycles, it was charged to 4 V and subjected to an ARC test.

[0058] ARC test conditions for battery cells: Start from 50℃ and enter the "heating-waiting-searching" mode, heat the battery in steps of 5℃, wait for 5 minutes, and if the battery's own temperature rise rate is detected to be greater than 0.02℃ / min, it is considered that the battery has started to self-heat.

[0059] Comparative Example 1

[0060] The difference between this comparative example and Example 1 is that 2 mL of 1M NaPF6, EC:DEC=1:1 Vol% electrolyte is injected into the battery cell.

[0061] Comparative Example 2

[0062] The difference between this comparative example and Example 1 is that: 5 mL 1M NaPF6, EC:DEC=1:1 Vol% electrolyte and 2 mL 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether are selected to prepare the electrolyte, and 2 mL of the electrolyte is injected into the battery cell.

[0063] Figure 1 The cell cycle performance diagrams of Example 1, Comparative Example 1 and Comparative Example 2 are shown. The test results show that the capacity retention rate of Example 1 is 91.6%, the capacity retention rate of Comparative Example 1 is 75.9%, and the capacity retention rate of Comparative Example 2 is 73.4%, indicating that siloxane participates in constructing a more stable negative electrode-electrolyte interface layer, thereby reducing capacity loss and improving cycle stability.

[0064] Comparative Example 3

[0065] The difference between this comparative example and Example 2 is that the electrolyte used is the electrolyte of comparative example 1, and the battery cell used is the battery cell that has completed the cycle of comparative example 1.

[0066] Figure 2 The thermal stability test results of Example 2 and Comparative Example 3 are shown. The test results show that the heat release of Example 2 is 41.4 J / g, while the heat release of Comparative Example 3 is 316.92 J / g, which is 7 to 8 times that of Example 2. This indicates that the addition of siloxane to the electrolyte of 1MNaPF6, EC:DEC=1:1Vol% can effectively inhibit the exothermic side reaction of hard carbon and electrolyte, and improve the thermal stability of the negative electrode-electrolyte interface layer.

[0067] Figure 3 The morphologies of the hard carbons of Example 2 and Comparative Example 3 under a scanning electron microscope are shown. It can be seen that the surface of the hard carbon of Example 2 is more uniform, indicating that siloxane can promote the formation of a uniform negative electrode-electrolyte interface layer.

[0068] Comparative Example 4

[0069] The difference between this comparative example and Example 3 is that a battery as described in Comparative Example 1 is prepared.

[0070] Table 1 Thermal runaway test data of Example 3 and Comparative Example 4

[0071]

[0072] Figure 4 Table 1 and ARC test results of Example 3 and Comparative Example 4 show that compared with Comparative Example 4, the self-exothermic temperature of the soft-pack battery in Example 3 is increased from 65.15°C to 110.10°C, and the maximum thermal runaway temperature is reduced from 312.90°C to 190.90°C, indicating that the addition of siloxane to the electrolyte effectively improves the thermal stability of the hard carbon-electrolyte interface layer of the NFM||HC battery cell, hindering its further combustion, and the time from self-heating to runaway heating is increased by 3.16h, indicating that the temperature rise rate is slowed down in this stage, which is conducive to leaving sufficient time for reaction and inhibiting further thermal runaway.

[0073] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A highly safe sodium ion battery electrolyte, characterized in that: Including sodium salts, carbonate solvents, and polycyclic siloxanes.

2. The sodium ion battery electrolyte according to claim 1, characterized in that The sodium salt is selected from sodium hexafluorophosphate or sodium perchlorate; the polycyclic siloxane is an organic small molecule monomer, a carbon chain is bonded to the polycyclic ring, the carbon chain contains fluorine atoms and silicon-oxygen bonds, and is liquid or solid at room temperature; the polycyclic ring in the polycyclic siloxane is a three-membered ring or a four-membered ring; the concentration of the sodium salt in the electrolyte is 0.5-3M, and the content of the polycyclic siloxane in the electrolyte is 5-10Vol%.

3. The sodium ion battery electrolyte according to claim 1, characterized in that The carbonate solvent is selected from two or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and propylene carbonate.

4. The sodium ion battery electrolyte according to claim 1, characterized in that The electrolyte further includes a dissolving agent.

5. The sodium ion battery electrolyte according to claim 4, characterized in that The dissolution promoter is selected from one or more of hydrofluoroethers such as 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, tris(trifluoroethoxy)methane, 1,1,1,3,3,3-hexafluoroisopropyl methyl ether, 1H,1H,5H-octafluoropentyl 1,1,2,2-tetrafluoroethyl ether and fluorinated aromatic 1,2-2 fluorobenzene.

6. The sodium ion battery electrolyte according to claim 1, characterized in that If the electrolyte is separated into layers after standing for 2-4 hours, 15-30 Vol% of a dissolving agent needs to be added, and stirring is continued for 4-6 hours; if the electrolyte is not separated into layers after standing, no dissolving agent needs to be added.

7. A sodium ion battery comprising the high-safety sodium ion battery electrolyte according to any one of claims 1 to 6.

8. The sodium ion battery according to claim 7, characterized in that The laminate is made by injecting high-safety sodium-ion battery electrolyte in an argon atmosphere with O2<0.5ppm and H2O<0.5ppm, and then heat-sealing after standing in vacuum for 6-10 hours.

9. The sodium ion battery according to claim 7, characterized in that: The invention comprises a positive electrode, a negative electrode and a separator, wherein the positive electrode is one of sodium nickel iron manganate, sodium nickel manganate, sodium manganate, sodium iron phosphate, sodium vanadium phosphate or sodium iron pyrophosphate, and the negative electrode is hard carbon; and the separator is polyolefin.

10. The sodium ion battery according to claim 7, characterized in that: The electrolyte injection coefficient in the sodium ion battery is 1.5-2.5 mL / Ah.

Citation Information

Cited By

  • Electrolyte for improving positive electrode performance of high-voltage sodium-ion battery as well as preparation method and application of electrolyte

    CN121565939A